Glutamatergic synaptic deficits in the prefrontal cortex of the Ts65Dn mouse model for Down syndrome - Thomazeau, Aurore; Lassalle, Olivier; Manzoni, Olivier J. (Frontiers in Neuroscience, 2023)
Down syndrome (DS), the most prevalent cause of intellectual disability, stems from a chromosomal anomaly resulting in an entire or partial extra copy of chromosome 21. This leads to intellectual disability and a range of associated symptoms. While there has been considerable research focused on the Ts65Dn mouse model of DS, particularly in the context of the hippocampus, the synaptic underpinnings of prefrontal cortex (PFC) dysfunction in DS, including deficits in working memory, remain largely uncharted territory. In a previous study featuring mBACtgDyrk1a mice, which manifest overexpression of the Dyrk1a gene, a known candidate gene linked to intellectual disability and microcephaly in DS, we documented adverse effects on spine density, alterations in the molecular composition of synapses, and the presence of synaptic plasticity deficits within the PFC. The current study aimed to enrich our understanding of the roles of different genes in DS by studying Ts65Dn mice, which overexpress several genes including Dyrk1a, to compare with our previous work on mBACtgDyrk1a mice. Through ex-vivo electrophysiological experiments, including patch-clamp and extracellular field potential recordings, we identified alterations in the intrinsic properties of PFC layer V/VI pyramidal neurons in Ts65Dn male mice. Additionally, we observed changes in the synaptic plasticity range. Notably, long-term depression was absent in Ts65Dn mice, while synaptic or pharmacological long-term potentiation remained fully expressed in these mice. These findings provide valuable insights into the intricate synaptic mechanisms contributing to PFC dysfunction in DS, shedding light on potential therapeutic avenues for addressing the neurocognitive symptoms associated with this condition.